2022
DOI: 10.3389/fcvm.2022.847286
|View full text |Cite
|
Sign up to set email alerts
|

Direct Oral Anticoagulants vs. Warfarin in Hemodialysis Patients With Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe use of Direct Oral Anticoagulants (DOACs) in patients who have both atrial fibrillation (AF) and end-stage renal disease (ESRD) requiring hemodialysis remains controversial, with warfarin remaining the mainstay of the treatment. As hemodialysis patients were excluded from most clinical DOACs trials, the evidence of their efficacy and safety is lacking in this cohort of patients.AimTo review the current evidence investigating safety profile and the efficacy of DOACs in comparison with warfarin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Contrary to previous studies, our study excluded patients with a history of stroke and transient ischemic attack; therefore, the CHA 2 DS 2 -VASc score was low (mean; 2.6 points versus 4.5 points). Previous studies had reported that no significant differences in the rates of ICH, GI bleeding, and MI between DOACs and warfarin 26,30,31 . In alignment with these previous studies, we found that ICH, GI bleeding, and MI were comparable between DOACs and warfarin.…”
Section: Discussionmentioning
confidence: 90%
“…Contrary to previous studies, our study excluded patients with a history of stroke and transient ischemic attack; therefore, the CHA 2 DS 2 -VASc score was low (mean; 2.6 points versus 4.5 points). Previous studies had reported that no significant differences in the rates of ICH, GI bleeding, and MI between DOACs and warfarin 26,30,31 . In alignment with these previous studies, we found that ICH, GI bleeding, and MI were comparable between DOACs and warfarin.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, a systematic review and meta-analysis conducted by El Far et al which included five large clinical studies, out of which three involved apixaban, evaluated the efficacy and safety of DOACs (n = 3044), as compared to warfarin (n = 31,472), in patients with NVAF on dialysis [ 13 ]; it showed a cumulative bleeding risk and mortality rate lower than those observed in our study (12.2% and 11.4%, respectively). Another small study by Sarrat et al which included 40 ESKD patients on chronic dialysis, although with no reported duration of apixaban use, showed a favorable risk profile for apixaban, with no major bleeding events [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the meta-analysis conducted by El Far et al included five studies, with a total of 31,472 (92.14%) patients on warfarin and 3044 (8.91%) patients on DOACs, and showed no significant differences in the incidences of hemorrhagic stroke, major bleeding, hemodialysis access site bleeding, ischemic stroke, or gastrointestinal bleeding between DOACs and warfarin-treated patients. However, patients who received DOACs presented with higher rates of systemic embolization, minor bleeding, and death events than was reported in the warfarin group ((3.39% vs. 1.97%, p -value = 0.02), (6.78% vs. 2.2%, p -value 0.02), and (11.38% vs. 5.12%, p -value < 0.006), respectively) [ 13 ]. Welander et al also showed that in a total of 2453 Swedish patients with NVAF and CKD G3-G5D, the DOAC-treated group (41%) showed a lower hazard of major bleeding [HR 0.71 (95% confidence interval 0.53–0.96)], but there was no difference in ischemic stroke risk, compared with the warfarin group (59%).…”
Section: Discussionmentioning
confidence: 99%
“…See et al reported no significant difference in effectiveness and safety outcomes between DOACs and warfarin in AF patients on dialysis [ 37 ]. In contrast, Elfar et al demonstrated that DOACs were associated with higher rates of systemic embolization, minor bleeding, and death compared to warfarin [ 38 ]. Conversely, Li et al found that DOACs were associated with a reduced risk of gastrointestinal bleeding [ 39 ].…”
Section: Discussionmentioning
confidence: 99%